Illiberal Peace in Sri Lanka: Reasons and Achievements of the Resulting Peace - Adhira, Putri; Triasari, Devi (Journal of Law, Environmental and Justice, 2024)
Sri Lanka is one example that is often raised in the literature to describe what then categorized as illiberal peace process. In this country, the illiberal peace process needs to be seen as an new political option from Presiden Mahinda Rajapaksa to end a prolonged civil war. This study focused to answer two questions: (1) the reasons why President Mahinda Rajapaksa more prefer choose illiberal peace and (2) the peace created after the war was stopped in Sri Lanka. The study found at least three reasons behind President Mahinda Rajapaksa illiberal decision: the issue about threat of prolonged domectic instability, the ineffectiveness of negotiations, and finally, about political opportunity. About peace after war, this study found Sri Lanka led to the formation of a negative peace order.